Remoción de cadmio en almendras de cacao (theobroma cacao l.) aplicando la enzima Pectintranseliminasa - Molina Triviño , Byron Fabian (2023)
Currently, cadmium content in cocoa beans is an issue that has gained the attention of many countries because it compromises health, the environment, food safety, and potentially limits exports. This research was carried out with samples of National and CCN51 cocoa collected at the "Isaías" farm in the Pasaje canton of El Oro province. The objective was to evaluate the method to remove cadmium concentrations in cocoa beans during the fermentation process by applying the enzyme pectintranseliminase and the influence on the physical, chemical, and organoleptic conditions, in addition, to compare the results obtained with research from countries belonging to America. The experimental study was a completely randomized design (CRD), with 11 treatments and 3 replicates for each cocoa variety. The enzyme was then applied, and each treatment went through its respective stages of pre-drying, washing, drying and resting.